A high resolution study of dynamic changes of Ce2O3 and CeO2 nanoparticles in complex environmental media - Merrifield, Ruth C.; Arkill, Kenton P.; Palmer, Richard E.; Lead, Jamie R. (American Chemical Society, 2017)
Ceria nanoparticles (NPs) rapidly and easily cycle between Ce(III) and Ce(IV) oxidation states, making them prime candidates for commercial and other applications. Increased commercial use has resulted in increased discharge to the environment and increased associated risk. Once in complex media such as environmental waters or toxicology exposure media, the same redox transformations can occur, causing altered behavior and effects compared to the pristine NPs. This study used high resolution scanning transmission electron microscopy and electron energy loss spectroscopy to investigate changes in structure and oxidation state of small, polymer-coated ceria suspensions in complex media. NPs initially in either the III or IV oxidation states, but otherwise identical, were used. Ce(IV) NPs were changed to mixed (III, IV) NPs at high ionic strengths, while the presence of natural organic macromolecules (NOM) stabilized the oxidation state and increased crystallinity. The Ce(III) NPs remained as Ce(III) at high ionic strengths, but were modified by the presence of NOM, causing reduced crystallinity and degradation of the NPs. Subtle changes to NP properties upon addition to environmental or ecotoxicology media suggest that there may be small but important effects on fate and effects of NPs compared to their pristine form.